PENINGKATAN KUALITAS TEMPOYAK TRADISIONAL JAMBI MELALUI FORTIFIKASI ZAT PENGENTAL DENGAN BERBAGAI KONSENTRASI - Addion Nizori; Hesi Novialispita; Surhaini Surhaini; Lavlinesia Lavlinesia (AGROINTEK, 2021)
Tempoyak powder is a fermented product of durian meat which is traditionally mixed with salt which is further processed through a fermentation process during storage. Maltodextrin is one of food additive, mainly used as a filler and emulsifier used in the manufacture of food powders because it has many functions in accelerating the drying process, helping in dispersing and trapping flavor of food products. This study aims to determine the best maltodextrin concentration against the physicochemical and organoleptic properties of tempoyak powder. This research was carried used a completely randomized design (CRD) with 6 treatment levels of maltodextrin concentrations which are 0, 5, 10, 15, 20 and 25% respectively, each treatment was repeated 3 times. Tempoyak powder was taken image using a scanning electron microscope (SEM) with JEOL JSM 6510 LA model. The results showed that the concentration of maltodextrin had a significant effect on yield, moisture content, color, total dissolved solids, pH, color organoleptic test, aroma and overall acceptance. The best maltodesktrin concentration in tempoyak powder is a concentration of 20% with a score of 4.16 (yellow) color, aroma 4.28 (typical tempoyak), taste 4.08 (sour) and an overall rating of 3.52 (somewhat like) which results in yield value 38.24%, moisture content 12.5781%, L value 43.61, oHue value 72.96 with a description of the color yellow red, total dissolved solids 67.67oBrix and pH 5.28.